Airways in Out-of-hospital Cardiac Arrest: Systematic Review and Meta-analysis. (3rd April 2014) - Fouche, Pieter F.; Simpson, Paul M.; Bendall, Jason; Thomas, Richard E.; Cone, David C.; Doi, Suhail A. R.
Abstract Objective. To determine the differences in survival for out-of-hospital advanced airway intervention (AAI) compared with basic airway intervention (BAI) in cardiac arrest. Background. AAI is commonly utilized in cardiac arrest in the out-of-hospital setting as a means to secure the airway. Observational studies and clinical trials of AAI suggest that AAI is associated with worse outcomes in terms of survival. No controlled trials exist that compares AAI to BAI. Methods. We conducted a bias-adjusted meta-analysis on 17 observational studies. The outcomes were survival, short-term (return of spontaneous circulation and to hospital admission), and longer-term (to discharge, to one month survival). We undertook sensitivity analyses by analyzing patients separately: those who were 16 years and older, nontrauma only, and attempted versus successful AAI. Results. This meta-analysis included 388, 878 patients. The short-term survival for AAI compared to BAI were overall OR 0.84(95% CI 0.62 to 1.13), for endotracheal intubation (ETI) OR 0.79 (95% CI 0.54 to 1.16), and for supraglottic airways (SGA) OR 0.59 (95% CI 0.39 to 0.89). Long-term survival for AAI were overall OR 0.49 (95% CI 0.37 to 0.65), for ETI OR 0.48 (95% CI 0.36 to 0.64), and for SGA OR 0.35 (95% CI 0.28 to 0.44). Sensitivity analyses shows that limiting analyses to adults, non-trauma victims, and instances where AAI was both attempted and successful did not alter results meaningfully. A third of all studies did not adjust for any other confounding factors that could impact on survival. Conclusions. This meta-analysis shows decreased survival for AAIs used out-of-hospital in cardiac arrest, but are likely biased due to confounding, especially confounding by indication. A properly conducted prospective study or a controlled trial is urgently needed and are possible to do.